A comparison of fatigue levels among Malaysian seafarers of different maritime sector - Mukhtar, Zaimi Zainal (2009)
This report is to identify the sources of fatigue and fatigue levels of Malaysian seafarers for different maritime sectors. The objective is to determine the sources of fatigue among seafarers from different sectors. Questionnaires are used to collect field data and then analyze using SPSS and MiniTAB. From the analysis, it was found that fatigue problem is caused by two main factors which are shift of work and seafarers’ working environment. The result proves the two factors caused fatigue to seafarers from different sectors where the score of mean for group of seafarers who work in Port (Mean=3.52 and 4.12), Coastal Container (Mean=3.80 and 3.61), Foreign-Tanker (Mean = 4.05 and 3.91) and Foreign-LNG (Mean =4.05 and 3.85) were classified as high score. Technology used onboard ship is one of the factor to take into consideration as a tool to overcome the fatigue problem at sea. The finding shows that respondents in Port (Mean =3.74), Coastal-Container (Mean =4.11), Foreign-Tanker (Mean = 4.14) and Foreign-LNG (Mean = 3.87) mostly agreed on the effect of technology at sea based on the high mean score.